The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/7897529
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Estimate the Joint Roughness Coefficient by Back Calculation of Shear Strength

Abstract: The joint roughness coefficient (JRC) is an important factor affecting the shear properties of rock joints, and its accurate estimation is a challenging task in rock engineering. Existing JRC evaluation approaches such as the empirical comparison method and the statistical parameter method have some unresolved defects. In this study, a new method is proposed for JRC estimation to overcome the deficiencies of existing approaches based on back calculation of shear strength. First, the 10 standard roughness joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Obviously, this procedure ignored the effect of the protrusion size on overall roughness. The distribution law of the external force borne by the joint protrusion was rarely mentioned in the existing literature, and there was no quantitative result for reference [34][35][36]. Moreover, the size of joint protrusion in rough joints is difficult to be clearly simulated, which leads to poor correlation of corresponding analysis results [37].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, this procedure ignored the effect of the protrusion size on overall roughness. The distribution law of the external force borne by the joint protrusion was rarely mentioned in the existing literature, and there was no quantitative result for reference [34][35][36]. Moreover, the size of joint protrusion in rough joints is difficult to be clearly simulated, which leads to poor correlation of corresponding analysis results [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study related to the effect of the structural plane roughness on the rockburst is still limited. Moreover, the results from previous studies showed that the shear strength increased with the increase in friction coefficient µ in the SJM [56,57], and the joint roughness coefficient (JCR) was positively correlated with the shear strength [58].…”
Section: Influence Of Structural Plane Roughnessmentioning
confidence: 95%
“…e average horizontal length of 10 standard roughness joint profiles was about 99 mm. According to the processing idea of Zheng and Qi [25] and Huan et al [35], the horizontal length of the 10 joint profiles Surface height (y) Figure 2: e diagram used to define geometric coordinates of a joint profile [12]. Advances in Civil Engineering was assumed to be 100 mm, and the JRC values of them were assumed to be unchanged.…”
Section: Digitization Of Ten Standard Roughness Profilesmentioning
confidence: 99%
“…In addition, the shear direction of rock joints periodically reversed under cyclic shear conditions. e shear strength values are usually not equal, although the joint morphology does not change much before the last shearing process [32][33][34][35]. In the JRC-JCS model proposed by Barton [10], JCS, normal stress, and basic friction angle are all parameters without direction property.…”
Section: Introductionmentioning
confidence: 99%